Pengaruh Pengelolaan Kelas Terhadap Motivasi Keaktifan Belajar Siswa di Sekolah SMA Negeri 22 Surabaya - Pramudya, Andhika; Nagita Dwi Erianti Prakoso; Zafira Nisa’ Azahra; Nadiva Zahra Atika Rahma; Indah Putri Purwanti; Kaniati Amalia (CV Putra Publisher, 2024)
Education is a lifelong learning process that includes formal, nonformal, and informal aspects, aiming to develop students' character, knowledge, and skills. Apart from being a means of knowledge transfer, education also plays a role in the formation of moral values and helps students adapt to the dynamics of the times. Teachers are the main actors in the success of education, playing a role not only as teachers, but also as facilitators and supervisors who are able to create a conducive learning environment and in accordance with the needs of students. This study aims to examine the influence of classroom management on student motivation and learning activity at SMAN 22 Surabaya. Education is a lifelong learning process that includes formal, nonformal, and informal aspects, aiming to develop students' character, knowledge, and skills. Apart from being a means of knowledge transfer, education also plays a role in the formation of moral values and helps students adapt to the dynamics of the times. Teachers are the main actors in the success of education, playing a role not only as teachers, but also as facilitators and supervisors who are able to create a conducive learning environment and in accordance with the needs of students. This study aims to examine the influence of classroom management on student motivation and learning activity at SMAN 22 Surabaya. Using a qualitative approach, data were collected through observation, semi-structured interviews, and documentation. The main teacher who became the focus of the research was Mr. Agus Suhendra, while the principal, Mr. Dr. Muhammad Romli S.Pd., M.Pd gave full support for the implementation of good classroom management in the school. The results of the study show that effective classroom management, such as the preparation of common rules, the application of project- and problem-based learning methods, and the group investigation approach, are able to increase student motivation and activeness in learning. Mr. Agus Suhendra gives individualized attention, uses interactive methods, and utilizes technology to create an interesting and supportive learning atmosphere. Good classroom management also includes maintaining the cleanliness and regularity of the learning environment. Students who study in a classroom with good management tend to be more active than students in a class with less than optimal management. In addition, students' internal factors such as interests, talents, and motivation also affect their involvement in the learning process. Mr. Agus Suhendra plays an important role in overcoming differences in student activity levels, by providing motivation, special attention, and awards. Interaction between students is also a factor that can spur their enthusiasm for learning. In the context of the independent curriculum, the use of diagnostic tests helps teachers understand student characteristics more deeply to create relevant and effective learning. With good classroom management by Mr. Agus Suhendra and policy support from Mr. Arif Hidayat, students' motivation and learning activity can be improved, as well as help them understand the importance of education to achieve optimal learning outcomes.